Economics of paternalism: the hidden costs of self-commanding strategies - Christophe Salvat (Editura ASE Bucuresti, 2015)
The paper proposes an economic assessment of paternalism by comparing different alternative responses to dynamically inconsistent behaviors consecutive to hyperbolic discounting. Two main types of action are possible, self-commanding strategies and paternalism The first category includes personal rules and pre-commitment The second can be subcategorized between coercive and non-coercive forms of paternalism, which are respectively associated (although it is debatable) with legal paternalism and with ‘nudges’. Despite being self-inflicted, self-commanding strategies are actually not cost free and can result in a dramatic cutback of people’s freedom of choice. Likewise, legal paternalism can, on occasion, be less harmful than personal rules or pre-commitment; similarly, nudges can be more invasive and less effective than their proponents want us to believe. The aim of this paper is not to propose any standardized form of response to irrational behavior (whatever that may mean) but to argue, on the contrary, that every case should be individually appraised. Individual situations can be remedied by self-commanding strategies or by paternalistic policies, either in isolation or in combination.